Kinematics of the Pamir and Hindu Kush regions from GPS geodesy. Issue 5 (8th May 2013) - Ischuk, Anatoli; Bendick, Rebecca; Rybin, Anatoly; Molnar, Peter; Khan, Shah Faisal; Kuzikov, Sergey; Mohadjer, Solmaz; Saydullaev, Umed; Ilyasova, Zhyra; Schelochkov, Gennady; Zubovich, Alexander V.
Abstract: [1] GPS velocities measured in the Pamir and surrounding regions show a total of ~30 mm/yr of northward relative motion between stable Pakistan and Eurasia. The convergence budget is partitioned into 10–15 mm/yr of localized shortening across the Trans‐Alai Thrust, which bounds the Pamir on the north, consistent with southward subduction of intact lithosphere. Another 10–15 mm/yr of shortening is distributed across the Chitral Himalaya and Hindu Kush, suggesting that Hindu Kush seismicity might be related to northward subduction of Indian lithosphere. Modest shortening at <5 mm/yr occurs north of the Trans‐Alai Thrust, across the South Tien Shan and between the Ferghana Valley and Eurasia. Negligible north‐south shortening occurs within the high Pamir, but as much as 5 mm/yr, and perhaps 10 mm/yr, of east‐west extension occurs within this region. This extension is matched by a comparable amount of east‐west shortening in the Tajik Depression. The localization of shortening to the margins of the Pamir combined with observations of distributed internal extension implies that the east‐west vertically averaged, horizontal compressive normal stress is smaller than the north‐south compressive stress. Key Points: There is a major surface zone of shortening corresponding to the Hindu Kush There are two marginal north‐south shortening zones bounding the Pamir East‐west extension of the Pamir matches shortening in the Tajik Depression